Tumour-like chagasic encephalitis in AIDS patients: an atypical presentation in one of them and outcome in a small series of cases - Sica, Roberto E. P. (2008)
Chagas' disease is an intracellular parasitic infection owed to a protozoarium, the Trypanosoma cruzi1, affecting a large population in Latinamerica. Within the region 15 to 16 million people are infected2. The worldwide pandemia, due to the infection of the HIV 1 virus, also affects Latinamerican countries. The number of patients with this condition in Central and South Americas amounts to 1.6 million persons3,4. Therefore, both illnesses overlap in a broad geographical area and may coincide in the same patient. The HIV infection, which causes the AIDS syndrome, impairs the immunological system and predisposes to the appearance of opportunistic infections, which may have been hosted unnoticed by the patient until then. Therefore, Chagas' disease, which is a dormant infection in most patients5, may reactivate if the immunological surveillance wanes off as the consequence of the viral insult. Along the last years we6,7 and others8-10 found patients afflicted by AIDS, who developed brain lesions yielded by the Trypanosoma cruzi. The present communication describes three further patients with this condition; one of them is unique because his clinical, radiological and immunological findings differ from those previously reported in the literature.